Sprache - Bewegung - Instruktion Multimodales Anleiten in Texten, audiovisuellen Medien und direkter Interaktion - Ortner, Heike (Sprache im Kontext / Language in Context, 2023)
We often acquire new movement patterns under expert guidance. This book discusses how this task is accomplished through multimodal means (linguistic, physical, visual levels). The Pilates method serves as the situational context. Using linguistic analysis methods, the practices of instructing are compared.